A new medium-bandgap fused-[1]benzothieno[3, 2-b][1]benzo-thiophene (BTBT) nonfullerene acceptor for organic solar cells with high open-circuit voltage. (17th December 2019) - Wang, Yunchuang; Chang, Meijia; Ke, Xin; Wan, Xiangjian; Yang, Guangcheng
Abstract: A new nonfullerene small molecule acceptor, namely DBTIC, based on an octocyclic thieno[3, 2- b ]thienodi(indenothiophene) unit using [1]benzothieno[3, 2- b ][1]-benzothiophene as the core unit, was developed. Despite the medium-bandgap of DBTIC (1.71 eV), a power conversion efficiency of 8.64% can be delivered by the solar cells combining DBTIC and a wide-bandgap polymer donor J52. The high open-circuit voltage ( V oc ) of 0.94 V is also rare for J52 based devices owing to the high-lying lowest unoccupied molecular orbital level of DBTIC. Moreover, using J71 with lower highest occupied molecular orbital level as polymer donor, a higher V oc up to 1.05 V can be achieved. Graphical abstract: Using [1]benzothieno[3, 2- b ][1]benzo-thiophene (BTBT) as the core unit, DBTIC exhibits medium-bandgap of 1.71 eV and achieves high V oc of 1.05 V. Image 1 Highlights: A new small molecule acceptor DBTIC using [1]benzothieno[3, 2- b ][1]-benzothiophene (BTBT) as the core unit was constructed. DBTIC exhibits a medium optical bandgap of 1.71 eV and a high-lying LUMO energy level of −3.73 eV. . The DBTIC -based solar cells could deliver a high V oc up to 1.05 V.